2003
DOI: 10.1021/jp0272973
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Time-Series Analysis of Photoinduced Fluorescence Oscillation in a Water Dispersion of Colloidal Quantum Dots

Abstract: We report on photoinduced fluorescence oscillation observed in a water dispersion of CdSe/ZnS core/shell quantum dots (QDs). The fluorescence intensity spontaneously oscillates under continuous excitation in a temperature-sensitive manner and emerges at 29-30 °C. The experimental results suggest that the fluorescence oscillation occurs only in the presence of QD aggregates. The oscillation is characterized by wavelet and nonlinear time-series analyses of the fluorescence intensity data at 30 °C. The results re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 46 publications
(59 reference statements)
2
14
0
Order By: Relevance
“…A photoinduced enhancement of PL-intensity has already been described for CdSe close-packed nanocrystal films, monolayers and organic solutions during broad-band VIS-illumination [15][16][17]. On our knowledge, this is a first report demonstrating an enhancement of PL-intensity of water-soluble CdSe nanocrystals during long-term UV-irradiation at physiological conditions.…”
Section: Introductionsupporting
confidence: 59%
“…A photoinduced enhancement of PL-intensity has already been described for CdSe close-packed nanocrystal films, monolayers and organic solutions during broad-band VIS-illumination [15][16][17]. On our knowledge, this is a first report demonstrating an enhancement of PL-intensity of water-soluble CdSe nanocrystals during long-term UV-irradiation at physiological conditions.…”
Section: Introductionsupporting
confidence: 59%
“…Previous studies have observed fluorescence oscillations in QD solutions, which were dependent upon salt concentration and temperature and had a period of B8 min. 32 These were attributed to interaction with ions in the solution. Our oscillations occurred on a faster time scale, but are consistent with the same explanation.…”
Section: Cdse/znsmentioning
confidence: 99%
“…, which was reduced to Ru(bpy) 3 2+ directly without light emission. Such a course inhibited the reaction of BrC • (COOH) 2 and Ru(bpy) 3 3+ from Process C. Consequently, the concentration of the Ru(bpy) 3 2+* was decreased and the generating rate of Br − was depressed, which resulted in a decrease in…”
Section: +mentioning
confidence: 99%
“…Since there are some obvious similarities between chemical oscillating systems and life processes that generally exhibit oscillatory behaviors, the investigation of the oscillating systems is of considerable interest. While a substantial number of chemical oscillators are known and have been widely used in analytical detection, [1][2][3][4][5][6][7][8][9][10][11][12][13][14] relatively few oscillating chemiluminescence (CL) reactions in the liquid phase have been described. [15][16][17][18][19][20] Recently, owing to the particular photochemical and photophysical properties of the tris(2,2′-bipyridine)ruthenium(II) [Ru(bpy) 3 2+ ] CL reagent, [21][22][23] the Ru(bpy) 3…”
Section: Introductionmentioning
confidence: 99%